KAMI index as an evaluation of academic information system security at XYZ university - Andi Sofyan Anas; I Gusti Ayu Sri Devi Gayatri Utami; Adam Bachtiar Maulachela; Akbar Juliansyah (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2021)
XYZ University is one of the universities that has used information technology to create quality service for students and the entire academic community. This Information technology service is managed by Information Technology and Communication Center (PUSTIK) which is responsible to carry out the development, management, service, and maintaining the security of information and communication technology. Good information technology governance should be able to maintain information security. Therefore, it is necessary to evaluate information system security especially the security of academic information systems. This information system security evaluation uses Keamanan Informasi (KAMI) Index which refers to the ISO/IEC 27001:2013 standard to be able to determine the maturity level of information security. An evaluation of five areas of the KAMI Index shows the Information Security Risk Management area gets the lowest score at 10 out of a total of 72. The result of the KAMI Index dashboard shows that the maturity level of each area of information security is at levels I and I+ with a total score of 166. This means that the level of completeness of implement ISO 27001:2013 standard is in the inadequate category.